2017
DOI: 10.1038/s41598-017-14976-8
|View full text |Cite
|
Sign up to set email alerts
|

Biomineral Nano-Theranostic agent for Magnetic Resonance Image Guided, Augmented Radiofrequency Ablation of Liver Tumor

Abstract: Theranostic nanoparticles based on biocompatible mineral compositions can significantly improve the translational potential of image guided cancer nano-therapy. Here, we report development of a single-phase calcium phosphate biomineral nanoparticle (nCP) with dual-mode magnetic resonance contrast (T1-T2) together with radiofrequency (RF) mediated thermal response suitable for image-guided RF ablation of cancer. The nanoparticles (NP) are engineered to provide dual MR contrast by an optimized doping concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…The iron doping causes a characteristic augmented ionic conductance which increases the dielectric loss of the NPs under the RF stimulation. This effect provokes a temperature rise responsible of the observed necrosis [86].…”
Section: Non-magnetic Npsmentioning
confidence: 99%
“…The iron doping causes a characteristic augmented ionic conductance which increases the dielectric loss of the NPs under the RF stimulation. This effect provokes a temperature rise responsible of the observed necrosis [86].…”
Section: Non-magnetic Npsmentioning
confidence: 99%
“…While our previous work has focused on targeted therapy 1 and drug delivery systems 2 to find new solutions for cancer therapy, in this work we consider the use of an innovative biotherapeutic approach using the therapeutic potential of stem cell secretions and creating a new formulation with translational potential. In this study, we use in vitro and in vivo models of triple negative breast cancer 3 (TNBC) lacking estrogen, progesterone and human epidermal growth factor 2 (HER2) receptors which is an aggressive form of breast cancer showing chemo 4 , 5 and immune resistant phenotype with poor response to targeted therapies 6 , 7 to evaluate the anti-cancer potential.…”
Section: Introductionmentioning
confidence: 99%
“…The lower-level values of the saturation magnetization of IronQ were responsible as a T1-positive contrast (bright image) agent for magnetic resonance imaging (MRI). T1-positive contrast agents, such as gadopentetate dimeglumine (Magnevist®), revealed Ms values equal to 0.397 emu/g at 1.2 T (12 kOe), while the Gd (III)-quercetin complex revealed Ms values equal to 0.405 emu/g at 1.5 T, and the iron (III)-doped calcium phosphate nanoparticles revealed Ms values that were lower than 0.15 emu/g at 1.5 T [ 71 73 ]. Notably, the higher levels (>20 emu/g) of the contrast agents, particularly superparamagnetic iron oxide nanoparticles (SPIONs), were observed as a superparamagnetic property and exhibited T2 negative (contrast dark image) in MR imaging [ 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…The paramagnetic properties of IronQ in the case study may be related to the five unpaired electrons found in the 3d orbit of iron (III) (high spin, S = 5/2), leading to an apparent effect identified as spin-lattice interactions under longitudinal relaxation at the applied magnetic field [ 73 ]. However, the oxidative state of iron (II) without the magnetic property did not affect T1 relaxation.…”
Section: Resultsmentioning
confidence: 99%